# What is the equation of the line tangent to # f(x)=-(x+2)^2-5-3# at # x=5#?

Utilizing the chain rule

The tangent line looks like this:

graph{[-285.2, 285.4, -142.6, 142.6]} = -(x+2)^(2)-8-y) = -12x+3-y

By signing up, you agree to our Terms of Service and Privacy Policy

The equation of the line tangent to f(x)=-(x+2)^2-5-3 at x=5 is y = -32x - 162.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- What is the instantaneous rate of change of #f(x)=(x-5)^2 # at #x=2#?
- What is the equation of the line tangent to # f(x)=x^3+4x^2+3x # at # x=3 #?
- What is the equation of the line tangent to #f(x)=x^2 sin2x # at #x=pi/4#?
- How do you find the equation of the tangent line to the graph of f(x) at given point if #f(x)= sqrt(x+1))# at (0,1)?
- What is the equation of the line tangent to # f(x)=-(x+2)^2-5-3# at # x=5#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7